246 Refractory seizures: a case of post-partum pyridoxine dependent epilepsy. Issue 12 (14th November 2019) - Chaudhuri, Shreya; Ball, Joanna; Murphy, Elaine; Muhammed, Kinan
Abstract : A 29 year old woman underwent a planned Caesarean delivery. She denied any pre-existing medical conditions. 72-hours later she developed multiple generalised tonic-clonic seizures requiring sedation and intubation. Brain imaging revealed long standing enlargement of the ventricles. Urinary protein and blood pressure were normal. She continued to have frequent seizures confirmed on EEG despite treatment with multiple anti-epileptics. Collateral history from family revealed seizures as an infant but none since aged 6 months and that she was not taking anticonvulsants. Further inquiries confirmed a regular prescription for Vitamin B6 (Pyridoxine) which she had stopped during pregnancy. In the context of refractory seizures and the imaging findings, the possibility of Pyridoxine-dependent epilepsy was raised. Pyridoxine 100 mg twice daily was started. After the first dose, the patient's seizures stopped and she was extubated, anticonvulsants were stopped and she had no further seizures. Pyridoxine dependent epilepsy is an autosomal recessive condition. Clinical features include refractory seizures in the first few months of life. It is caused by mutations in the ALDH7A1 gene which codes for α-aminoadipic semialdehyde dehydrogenase (α-AASA, Antiquitin), an enzyme involved in the breakdown of lysine within the brain resulting in raised levels. Diagnosis involves genetic testing and elevated plasma and urine levels of α-AASA. Treatment is lifelong daily pyridoxine supplementation. Pabrinex containing Pyridoxine should be considered in all patients who have ongoing seizures not responding to multiple anti-epileptic medication.